Ectopic Literature and Literature of Exile: Theoretic Notes (Castilla. Estudios de Literatura, 2013)
In the present article we investigate the ectopic literature based on the definition proposed by professor Tomás Albaladejo Mayordomo in the article “Sobre la literatura ectópica”. Using the ideas expressed in the cited article, we try to establish the theoretic-literary difference between the ectopic literature and literature of exile, illustrating with some cases of XX century Russian literature of exile.